The development and initial evaluation of katatagan a resilience interventionfor Filipino disaster survivors - Hechanova, Ma. Regina M. (Philippine Journal of Psychology, 2015)
This paper documents the development, pilot, and initial evaluation of Katatagan, a group-based resilience program designed to hone coping skills of Filipino disaster survivors. The paper describes vulnerabilities and protective factors of Filipino survivors based on previous research and key informant interviews. It also explains how Luthar and Cicchetti’s (2000) resilience framework and guidelines for the development of interventions were incorporated in the objectives and the design of the resilience intervention. The intervention consists of six modules that aim to improve self-efficacy, adaptive coping skills, and well-being of Filipino survivors. The paper presents an initial evaluation of Katatagan among college students in Tacloban. Results revealed significant improvements in adaptive coping behaviors and a decrease in anxiety and depressive symptoms. Although more robust evaluations are necessary, the results provide encouraging evidence for the value of group-based and culturally-nuanced interventions. Moreover, the paper describes a collaborative and systematic process of designing a needs- based resilience interventions for Filipino disaster survivors.